A Review on Metric Symmetries Used in Geometry and Physics. (27th March 2012) - Duggal, K. L.
Abstract : This is a review paper of the essential research on metric (Killing, homothetic, and conformal) symmetries of Riemannian, semi-Riemannian, and lightlike manifolds. We focus on the main characterization theorems and exhibit the state of art as it now stands. A sketch of the proofs of the most important results is presented together with sufficient references for related results.